Hubungan Antara Subjective Well-Being dengan Burnout pada Tenaga Medis Di Masa Pandemi Covid-19 - Pertiwi, Mahesti; Andriany, Anissa Rizky; Pratiwi, Ajheng Mulamukti Asih (Syntax Idea, 2021)
The purpose of study was to analyze the subjective well-being and the burn out of medical personnel during the pandemic Covid-19. The method used in this research is quantitative with the type of correlational test research, which is a study used to find the relationship between two or more variables. Based on the results of the research, it was found that the level of subjective well-being on medical personnel during the covid-19 pandemic was at the low level of 37.5%, while the moderate level of 31.25% and at the high level of 31.25%. The factors that influence subjective well-being consist of gender, goals, religion or spirituality, social relationship quality factors, and personality. Based on the results of the research conducted, it can be concluded that subjective well-being has a correlation with burnout. There is a negative relationship between subjective well-being and burnout in medical personnel during the Covid-19 pandemic, namely the higher the subjective well-being the lower the burnout, and vice versa.